Analisis Tata Niaga Produk Agroindustri Gula Semut di Kabupaten Kulon Progo - Hertini, Etty Sri; Hermantoro, Hermantoro; Manumono, Danang (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
Brown sugar is one of the palm derivative products that have high economic value and has very good prospects for development. Commerce is a trading activity that combines the flow of goods and services from the level of production to consumption. This study aims to determine the share margin received by each channel of the brown sugar commerce at Kulon Progo Regency. This research, which was conducted in May-July 2020, used a descriptive method. The method of determining the research location used the purposive sampling method. Determination of the number of informants is determined by the snowball method with a total of 60 informants. Methods of data analysis using cost analysis tools and marketing margins. The results showed that the marketing margin obtained at the farm level was Rp1.706/kg while the collectors were Rp4.375/kg. Product variations being developed are printed coconut sugar, wet neutral brown sugar, dry neutral brown sugar, and flavor variants.